2013
DOI: 10.1186/2051-5960-1-67
|View full text |Cite
|
Sign up to set email alerts
|

Focal cortical dysplasias in autism spectrum disorders

Abstract: BackgroundPrevious reports indicate the presence of histological abnormalities in the brains of individuals with autism spectrum disorders (ASD) suggestive of a dysplastic process. In this study we identified areas of abnormal cortical thinning within the cerebral cortex of ASD individuals and examined the same for neuronal morphometric abnormalities by using computerized image analysis.ResultsThe study analyzed celloidin-embedded and Nissl-stained serial full coronal brain sections of 7 autistic (ADI-R diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 59 publications
2
87
0
9
Order By: Relevance
“…Further, abnormalities in local circuits could impede the formation of long-distance connectivity between various, functionally specialised parts of the cortex , resulting in significant hypo-or under-connectivity crosscortically (Casanova et al, 2002;Courchesne & Pierce, 2005;Lewis & Elman, 2008;Rubenstein & Merzenich, 2003). The model is now being supported at the cytoarchitectural level (Casanova et al, 2013;Casanova & Trippe, 2009;Stoner et al, 2014) with additional support from in vivo measures of GABA in ASD populations (Gaetz et al, 2014). However, a recent review of neurophysiological and psychophysiological research into alterations in the balance of excitation-inhibition in ASD has concluded that, while the evidence for an imbalance is strong, it may arise not only from excitation being increased relative to inhibition (as above) but also from increased inhibitory processes resulting in imbalance relative to excitatory processes (Dickinson, Jones, & Milne, 2016).…”
Section: Excitation-inhibition In Autismmentioning
confidence: 91%
“…Further, abnormalities in local circuits could impede the formation of long-distance connectivity between various, functionally specialised parts of the cortex , resulting in significant hypo-or under-connectivity crosscortically (Casanova et al, 2002;Courchesne & Pierce, 2005;Lewis & Elman, 2008;Rubenstein & Merzenich, 2003). The model is now being supported at the cytoarchitectural level (Casanova et al, 2013;Casanova & Trippe, 2009;Stoner et al, 2014) with additional support from in vivo measures of GABA in ASD populations (Gaetz et al, 2014). However, a recent review of neurophysiological and psychophysiological research into alterations in the balance of excitation-inhibition in ASD has concluded that, while the evidence for an imbalance is strong, it may arise not only from excitation being increased relative to inhibition (as above) but also from increased inhibitory processes resulting in imbalance relative to excitatory processes (Dickinson, Jones, & Milne, 2016).…”
Section: Excitation-inhibition In Autismmentioning
confidence: 91%
“…A future extension of this work would be analyzing the extracted brain and testing these measurements not only to diagnose autism [191][192][193][194][195][196][197][198], but also to characterize physiological processes and other disease entities or to characterize the severity of other diseases such as dyslexia [199,200], attention deficit disorder (ADD), brain tumors, strokes, seizure disorders, depression, and Alzheimer's disease [201].…”
Section: B Future Workmentioning
confidence: 99%
“…• A future work of this dissertation is to investigate the integration of the proposed work with the BioImaging lab work for the detection of other brain disorders such as autism [313,[336][337][338][339][340][341][342][343].…”
Section: B Directions For Future Researchmentioning
confidence: 99%